Creation of metal materials nanoporous structures under the action of laser radiation - Murzin, S.P.; Kazanskiy, N.L. (ALT Proceedings, 2026)
The laser radiation exposure for creation ofnanoporous structures in the Cu-Zn alloy wasstudied. Exposure to laser pulse-periodic radiationwith pulse repetition rate up to 5000 Hz makes itpossible to form a nanoporous structure in the nearsurfacelayer. The modes of an increase of the areadepth of such structures formation up to 40...45 μmwere ascertained. The temperature and speed modeswhich provide predominant channel-type nanoporesformation with widths of about 100 nm forming ananoporous net were investigated.